2002
DOI: 10.1046/j.1442-2042.2002.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of adrenomedullin induced by hypoxia in angiogenesis in human renal cell carcinoma

Abstract: Background : Adrenomedullin (AM) has pluripotent activities and is involved in the regulation of vasomotor tone, cell differentiation and embryogenesis. However, the expression and pathophysiological role of AM has not been determined in human renal cell carcinoma (RCC). Methods : Twenty-six RCC specimens and three cultured human RCC cell lines (A498, SN12C and KPK-13) were analyzed. Expression of AM was determined by immunohistochemistry and reverse transcription-polymerase chain reaction (RT-PCR) analysis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 33 publications
4
31
0
Order By: Relevance
“…HIF-1-inducible genes include angiogenic factors such as vascular endothelial growth factor (VEGF), platelet-derived growth factor, basic fibroblast growth factor, and adrenomedullin (AM) (4,5). Among these angiogenic factors, we have been examining the role of AM in tumor formation by pancreatic cancer cells, and found that the increase in the AM mRNA level under hypoxia was markedly greater than that in the VEGF mRNA level in accordance with a previous report (6). We demonstrated that the intratumoral injection of an adrenomedullin antagonist (AMA) inhibited tumor growth in a pancreatic cancer cell line in a xenograft mouse model (7).…”
Section: Introductionsupporting
confidence: 49%
“…HIF-1-inducible genes include angiogenic factors such as vascular endothelial growth factor (VEGF), platelet-derived growth factor, basic fibroblast growth factor, and adrenomedullin (AM) (4,5). Among these angiogenic factors, we have been examining the role of AM in tumor formation by pancreatic cancer cells, and found that the increase in the AM mRNA level under hypoxia was markedly greater than that in the VEGF mRNA level in accordance with a previous report (6). We demonstrated that the intratumoral injection of an adrenomedullin antagonist (AMA) inhibited tumor growth in a pancreatic cancer cell line in a xenograft mouse model (7).…”
Section: Introductionsupporting
confidence: 49%
“…AM also promotes tumor angiogenesis and enhances VEGF [35], and MMP-2 [36] levels, and is highly expressed in hypoxic tumors [37,38]. In renal cell carcinoma cells, hypoxia leads to AM and VEGF expression, which act in a coordinate way to facilitate cell growth [37]. All this could have therapeutical implications in cancer treatment, since it seems clear from different studies that AM provides resistance to stress and induced-cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, AM could represent a putative tumor marker to predict response to radio-or chemotherapy, although this possibility has not been yet tested. AM also promotes tumor angiogenesis and enhances VEGF [35], and MMP-2 [36] levels, and is highly expressed in hypoxic tumors [37,38]. In renal cell carcinoma cells, hypoxia leads to AM and VEGF expression, which act in a coordinate way to facilitate cell growth [37].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated by several groups that ADM is protumorigenic by stimulating carcinoma cell growth and angiogenesis directly (Fujita et al, 2002;Hague et al, 2000;Martinez et al, 2002;Oehler et al, 2002;Ishikawa et al, 2003). As such, ADM is identified as a novel target for antiangiogenic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Human breast cancer cell lines overexpressing ADM displayed an increased angiogenic potential both in vitro and in vivo (Martinez et al, 2002). ADM and vascular endothelial growth factor (VEGF) are the most widely expressed angiogenic factors in uterine leiomyomas (Hague et al, 2000), while ADM expressed in human renal cell carcinoma is induced by hypoxia and coexpression of ADM and VEGF, indicating that ADM may increase blood flow by vasodilation in the tumor vessels induced by VEGF and subsequently promote tumor growth (Fujita et al, 2002). Ishikawa et al (2003) demonstrated that ADM antagonist significantly reduced the in vivo growth of a pancreatic cancer cell line indirectly, by suppressing the formation of large functional blood vessels in the tumor tissues, leading to depletion of nutrient and oxygen supply.…”
Section: Introductionmentioning
confidence: 99%